Exploring the Attitudes and Practices Regarding Alternative Revenue Streams among Indian Dental Professionals - A cross-sectional analysis - R, Kesavan; Natarajan, Prabhu Manickam; Mary, A Vinita; Umapathy, Vidhyarekha; Swamikannu, Bhuminathan (Bangladesh Journal of Medical Science, 2024)
Background: This study aimed to explore the attitudes and practices of dental professionals regarding alternative sources of revenue through a descriptive cross-sectional design and to explore other demographic factors which influence them. Materials and Methods: A Descriptive Cross-Sectional study was conducted among 400 dental professionals selected using stratified random sampling and were approached either personally or through electronic medium to fill a pre-tested validated questionnaire assessing their attitudes and practices towards alternative sources of revenue. The data were analysed using IBM SPSS Statistics Version 26.0. Cross tabulations were made and statistical significance was assessed using Pearson’s Chi-square test and Fisher’s exact test. A Binary Logistic Regression model was developed to predict the practice of alternative sources of revenue based on gender, qualification, occupation, and experience. Results: The results showed that about 36% of the participants are currently pursuing alternative sources of income with a significantly higher percentage of females involved (p=0.005). Most of the participants (37.6%) reported investing in stocks and finance followed by real estate, food industry, career guidance, product development etc. Around two-thirds of females reported being unsatisfied with their current income from dentistry and they have 1.76 times the odds of pursuing alternative sources compared to males (p=0.022). Undergraduate dentists have 2.51 times the odds of practicing other means of revenue. Conclusions: The study concludes that a substantial percentage of respondents had pursued alternative sources of revenue. Policymakers and educators can use these findings to develop strategies to promote entrepreneurship and financial literacy among dental professionals. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S9-S19